Effects of Capital Structure on Financial Performance of Deposit-Taking Saccos in Embu County - Alulu, Walter (University of Embu, 2019)
This research sought to determine the effects of capital structure on financial performance of deposit taking SACCOS in Embu County. Capital structure refers· to how firms fund their operations to enable them continue existing and grow. Many researchers have conducted research on capital structure but have left many gaps that thi research sought to close them. The main objective of the research was the effects of debt, equity and retained earnings on financial performance of SACCOS. Causal research design was used to conduct the research. All the 6 deposit taking SACCOS in Embu County were selected for study hence no sampling was done. 46 questionnaires were administered for data collection. SPSS' software was used to analyze data. Debt had a significant effect on financial performance with a p-value of 0.020, equity had a significant effect on the financial performance with a p-value of 0.021 while retained earnings had no significant effect on financial performance with p-value of 0.73. In addition, the study showed that equity is the cheapest source of capital followed by debt. The research concluded and recommended that firms should strive to maintain an optimal capital structure.